PENERAPAN MODEL PEMBELAJARAN MEA END ANALYSIS UNTUK MENINGKATKAN KEMAMPUAN MENYELESAIKAN SOAL ELASTISITAS DAN HUKUM HOOKE - Chintia Ayu Pratiwi; Haratua Tiur Maria; Syukran Musyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aims to indentify the effectiveness of the implementation of Means End Analysis (MEA) Learning models to improving students problem solving abilities in Elasticity and Hooke Law in SMK-SMTI Pontianak. The research method used was Pre-Experimental Design with the design of One-Group Pretest- Posttes. The samples were students of class X TP 1 with total of 30 students selected using Intact Grup. The student’s solve problems abilities were measured using 5 instrument test essay. Obtained data problem solving abilities of students before given treatment (pretest) with an average percentage of 27,61% categorized as very less and has increased to 82.06% categorized as very good. Wilcoxon statistical test results obtained Asym.sig 2-Tailed of 0,000 (<0.05) which shows that there are significant differences in the students' pretest and posttest results. The effectiveness of the application of the MEA learning model was calculated by using the Cohen effect size formula and the results obtained were 2,34 and classified as high. The implementation of the MEA learning model can be used as an alternative in improving students' ability to solve problems, especially about Elasticity and Hooke Law.Keyword : Ability of solving problem, Elasticity and Hooke Law, MEA